2021
DOI: 10.1177/23312165211031751
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Infants: Why and How

Abstract: In children with congenital deafness, cochlear implantation (CI) prior to 12 months of age offers the opportunity to foster more typical auditory development during late infancy and early childhood. Recent studies have found a positive association between early implantation and expressive and receptive language outcomes, with some children able to achieve normal language skills by the time of school entry. Universal newborn hearing screening improved early detection and diagnosis of congenital hearing loss, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 102 publications
0
13
0
Order By: Relevance
“…Nicholas et al also analyzed vocabulary, expressive and receptive language at 4.5 years of age and showed that children implanted between 6 and 11 months ( n = 27) achieved higher scores on all measures compared to those implanted between 12 and 18 months ( n = 42) [ 39 ]. Numerous studies demonstrated similar results regarding improved language trajectories among infants implanted <12 months [ 27 , 38 , 40 , 41 , 42 , 43 ]. However, Leigh et al showed no significant difference in the rate of receptive language growth between children implanted <12 months compared to those implanted between 13 and 24 months [ 44 ].…”
Section: Discussionmentioning
confidence: 80%
“…Nicholas et al also analyzed vocabulary, expressive and receptive language at 4.5 years of age and showed that children implanted between 6 and 11 months ( n = 27) achieved higher scores on all measures compared to those implanted between 12 and 18 months ( n = 42) [ 39 ]. Numerous studies demonstrated similar results regarding improved language trajectories among infants implanted <12 months [ 27 , 38 , 40 , 41 , 42 , 43 ]. However, Leigh et al showed no significant difference in the rate of receptive language growth between children implanted <12 months compared to those implanted between 13 and 24 months [ 44 ].…”
Section: Discussionmentioning
confidence: 80%
“…There is consensus that cochlear implants are largely safe across all age groups with congenital and acquired hearing loss, even for very young children ( Rajan et al, 2018 ; Uecker et al, 2019 ; Sharma et al, 2020 ; Deep et al, 2021 ; Naik et al, 2021 ; Purcell et al, 2021 ). The survival rates for cochlear implants are as follows [ Lane et al (2019) : 10-year cumulative survival rates 97.2%; Chen et al (2022) : 10-year rate 96.8%, 20-year rate 96.7%].…”
Section: Perspective: Cochlear Implant-specific Risks Can Be a Burden...mentioning
confidence: 99%
“…Numerous studies indicate that children and adolescents with congenital or early onset severe and profound hearing loss benefit from CI: it provides a clear benefit in the development of brain regions associated with hearing ( Sharma et al, 2002 ; Kral and Sharma, 2012 ; Kral et al, 2016 ; Cardon and Sharma, 2019 ; Lee et al, 2020 ; Wang et al, 2021 ) and supports auditory development ( Purcell et al, 2021 ) as well as the development of spoken language ( Percy-Smith et al, 2008 ; Peters et al, 2010 ; Geers et al, 2016 ). In particular, very early implantation ( Dettman et al, 2016 ; Ruben, 2018 ; Sharma et al, 2020 ; Naik et al, 2021 ) and bilateral implantations ( Lieu et al, 2020 ; Sharma et al, 2020 ) benefit the development of verbal language.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of auditory recovery, hearing aids and cochlear implantation are the main options in auditory rehabilitation. In congenital hearing loss, cochlear implants should be applied in younger, rather than older children, as prognosis for effective cochlear implant decreases over time (Karltorp et al, 2020;Kral & Sharma, 2012;Lyness et al, 2013;Purcell et al, 2021;Sharma & Campbell, 2011). However, even then, the success of their application might be dependent on the level of the reorganization of the AC: an early work showed that in children prior to cochlear implantation the level of metabolism in their cortex, including the AC, predicted their speech perception outcomes (D. S. Lee et al, 2001), suggesting a challenge posed by reorganization to intact sensory restoration.…”
Section: Introductionmentioning
confidence: 99%